Romantic Relationships and Self-Identification Process among LGBTQ+ Youth in Hanoi - Do Thanh Lan; Dao Thuy Hang (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Romantic relationships among LGBTQ+ youth highlight the diversity of sexual orientations and affirm the fundamental right to pursue happiness, thereby gradually challenging traditional notions of compulsory heterosexuality in modern society. The initiation and development of romantic relationships play a critical role in encouraging individuals to explore and better understand their sexualities. However, non-heterosexual relationships still face numerous obstacles, as many LGBTQ+ individuals lack a solid foundation for accurately understanding their identities. This qualitative study explores how romantic feelings and sexual experiences influence the self-identification process of LGBTQ+ youth. It draws on in-depth interviews with 16 LGBTQ+ individuals aged 21–25 living in Hanoi. The findings suggest that romantic relationships, both positively and negatively, shape individuals’ progression through the stages of self-identification—from initial awareness to eventual self-acceptance. These insights provide a foundation for future quantitative research to expand the scope and generalizability of the results. Received 15th December 2024; Revised 5th March 2025; Accepted 12th April 2025